Digital-based human resources training for DPD KNPI Papua Province in the Tanah Tabi customary region - Susi Marianingsih; Rizkial Achmad; Marla Sheilamita Shalin Pieter; Evanita Veronica Manullang; Rosalin Theophilia Tayane; Widodo Widodo; Mohammad Rahmat Irji Matdoan; Mursid Mursid; Yulius Palumpun (Community Empowerment, 2023)
The need for competent human resources in the field of digital technology in the current digital era is crucial. The Regional Board of the National Youth Committee (DPD KNPI) of Papua Province, a youth organization that plays an important role in the development of Indonesia, particularly in Papua Province, faces this challenge in the digital era. Therefore, this community service aims to provide digital training to KNPI members in the Tanah Tabi customary region, which includes Jayapura Regency, Jayapura City, Keerom Regency, and Sarmi Regency. The implementation method of this community service is divided into three stages: preparation, implementation, and evaluation. The results of this training demonstrate an improvement in the participants' abilities. Prior to the training, only 11% of the participants were proficient in using digital applications, but after the training, the number of proficient participants increased to 39%.